If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -7 = 11 + -3x Reorder the terms: -7 + x = 11 + -3x Solving -7 + x = 11 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -7 + x + 3x = 11 + -3x + 3x Combine like terms: x + 3x = 4x -7 + 4x = 11 + -3x + 3x Combine like terms: -3x + 3x = 0 -7 + 4x = 11 + 0 -7 + 4x = 11 Add '7' to each side of the equation. -7 + 7 + 4x = 11 + 7 Combine like terms: -7 + 7 = 0 0 + 4x = 11 + 7 4x = 11 + 7 Combine like terms: 11 + 7 = 18 4x = 18 Divide each side by '4'. x = 4.5 Simplifying x = 4.5
| -14-16=-2(d+8)-12d | | 2(y-7)=2y-38 | | q=c+d/2 | | 4/-x-3.2/-x-2+2/-5 | | (8x^3/14x)(7/4x) | | 3-5=1 | | 7-4x+1=5x-1 | | (2y-6)/4=(50*12)+5 | | 6t-4=2[(2+1)t-2] | | 10x=1500 | | 20b=1500 | | x+56/7=11 | | 10x=1800 | | -8=22t+-6t^2 | | 6n-5=-3n+22 | | 10x=2000 | | 20b=1000 | | 6t^3-2t^2-14t+8/3t-4=v | | 2x+13y=-29 | | v=6t^3-2t^2-14t+8/3t-4 | | 20b=2100 | | 4h-12=3h+7 | | x+x+4+8x+x-4+2x+2+3x-5+4x-10=360 | | 5x+3=9-1 | | X-10/3+1/2=-11/6 | | 8x-5+x=67 | | (x+7)*(x+5)=3 | | 1x^2+2x+(-0.5)=0 | | (2x+2)+(3x+4)+(4x+3)=180 | | x^2-25/3x+6 | | 2x/7=42 | | 8/9=4x |